A STUDY ON STUDENTS’ SCANNING ABILITY IN READING DESCRIPTIVE TEXT AT SECOND YEAR OF SMPN 1 TEMBILAHAN - Rusnida Rusnida; Melda Yeni (Fakultas Keguruan dan Ilmu Pendidikan, 2017)
The main purpose of this study was to know the students’ scanning ability in reading descriptive text. This research was conducted in the second year of SMPN 1 Tembilahan in November 2016. It was a descriptive research and used random sampling technique in selecting the sample. The total of the population in this research were 201 students and the researcher took 100 students or half of them to be the sample in this research. The data were collected by using a test in multiple choices. By the test, the researcher got the result that the students are able to find out the name of persons, numeric data, and the name of the place in reading descriptive text with the total mean score is 82.3 or in Very Good category level. The mean score of students’ scanning ability in reading descriptive text is different in each indicator, the students’ scanning ability in finding out name of person in reading descriptive text was 73.39, the students’ scanning ability in finding out numeric data in reading descriptive text was 83.14, and the students’ scanning ability in finding out name of place in reading descriptive text was 89.95. As a conclusion, by scanning the students understood and were able to find out the name of the person, numeric data, and the name of the place in reading descriptive text.